Synthesis and characterization of cellulose and hydroxyapatite-carbon electrode composite for trace plumbum ions detection and its validation in blood serum - Ajab, H. (Elsevier B.V., 2018)
A novel synthesis and characterization of cellulose, hydroxyapatite and chemically-modified carbon electrode (Cellulose-HAp-CME) composite was reported for the analysis of trace Pb(II) ions detection and its validation in blood serum. The Field Emission Scanning Electron Microscopy (FESEM) analyses showed that the composite retained the orderly porous structure but with scattered particle size agglomeration. The Fourier Transform Infrared Spectroscopy (FTIR) spectra suggested the presence of functional groups associated with the bending and stretching of carbon bonds and intermolecular H-bonding. Xâray Diffraction (XRD) analyses further elucidated that the crystallite size could have influenced the properties of the electrode. Based on Thermo-gravimetric Analysis (TGA/DTG), the composites showed thermal stability with more than 60 residual content at 700 Â°C. The sensor was successfully developed for trace Pb(II) ions detection in complex medium such as blood serum, in the physiologically relevant range of 10â60 ppb, with resulting Limit of Detection (LOD) of 0.11 Â± 0.36 ppb and Limit of Quantification (LOQ) of 0.36 Â± 0.36 ppb. The newly fabricated electrode could be advantageous as a sensing platform with favourable electrochemical characteristics for robust, in situ and rapid environmental and clinical analyses of heavy metal ions. Â© 2018